The Effect of Aqueous Extract of Sutherlandia frutescens (Unwele) and Benzathine Penicillin on Enterococcus faecalis - N. W. Nsele; S. Moodley (Challenges and Advances in Pharmaceutical Research Vol. 10, 2022)
Therapeutic plants have been used, for many years, traditionally for treatment of infections. The mounting growth of antimicrobial resistance, currently, has led to scientists exploring their antibacterial activity to form an essential part of alternative treatments. Aim: To assess the action of the combination of the aqueous extracts of Sutherlandia frutescens (S. frutescens) and benzathine penicillin on Enterococcus faecalis (E faecalis) using disc diffusion and microdilution methods. Method: Leaf extract, of S. frutescens, were prepared according to modified method of the German Homeopathic Pharmacopoea. The antibacterial activity of the combination, of the plant extract and benzathine penicillin, was evaluated using the disk diffusion test. The combination, of plant extract and penicillin, was in the ratio of 1:1. Results showing any form of inhibition were confirmed, by the minimum inhibitory concentration assays, using the agar dilution method. Bacterial sensitivity testing was performed in accordance with modified Kirby-Bauer antimicrobial sensitivity test. The combination and penicillin were all tested against E faecalis and, the results were compared to determine the synergistic or antagonistic activity. Results: Benzathine penicillin inhibited the bacteria producing a zone of inhibition which was equal to 27 mm. The zones of inhibition for the combination of extract and benzathine penicillin, against E faecalis, was 21 mm. The minimum inhibitory concentration, of the combination, was 0% growth for 1 in 2 to 1 in 16 dilutions. This clearly indicates an antagonistic activity. Conclusion: The potential for developing antimicrobials from plants, in vitro, provides a platform for phytomedicine and pharmacological studies.